2012
DOI: 10.3399/bjgp12x659330
|View full text |Cite
|
Sign up to set email alerts
|

Reasons why doctors choose or reject careers in general practice: national surveys

Abstract: BackgroundLess than one-third of newly qualified doctors in the UK want a career in general practice. The English Department of Health expects that half of all newly qualified doctors will become GPs. AimTo report on the reasons why doctors choose or reject careers in general practice, comparing intending GPs with doctors who chose hospital careers. Design and settingQuestionnaire surveys in all UK medical graduates in selected qualification years. MethodQuestions about specialty career intentions and motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 9 publications
5
47
0
4
Order By: Relevance
“…10 Also, many doctors are attracted to general practice for lifestyle reasons, and this factor is increasingly important for more recent graduates. [10][11][12] That females reported slightly higher job satisfaction than males is consistent with other research which has reported higher job satisfaction among female GPs. 13,14 The slightly more negative scores on job satisfaction of the doctors who first decided on a career in general practice late, after year 5, need cautious interpretation.…”
Section: Comparison With Existing Literaturesupporting
confidence: 81%
“…10 Also, many doctors are attracted to general practice for lifestyle reasons, and this factor is increasingly important for more recent graduates. [10][11][12] That females reported slightly higher job satisfaction than males is consistent with other research which has reported higher job satisfaction among female GPs. 13,14 The slightly more negative scores on job satisfaction of the doctors who first decided on a career in general practice late, after year 5, need cautious interpretation.…”
Section: Comparison With Existing Literaturesupporting
confidence: 81%
“…3 Doctors rejecting general practice as a speciality tended to cite reasons such as job content and too much administration. 4 One study found that junior doctors perceived general practice negatively and as a career with less clinical interest, but a better lifestyle. 5 However, a study at Imperial College Medical School in 2002 showed that students had a positive attitude towards general practice.…”
Section: Introductionmentioning
confidence: 99%
“…In a study performed by Lambert et al, enthusiasm for and commitment to the specialty' was a very important determinant of choice for intending doctors, regardless of their chosen specialty. Relatively few doctors had actually considered general practice seriously, but had then rejected it (13). Moreover, 78% of the doctors who rejected general practice presented 'job content' as their reason, compared with the 32% of doctors who rejected other specialties (13).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few doctors had actually considered general practice seriously, but had then rejected it (13). Moreover, 78% of the doctors who rejected general practice presented 'job content' as their reason, compared with the 32% of doctors who rejected other specialties (13). Therefore, the aim of this study was to compare the attitudes of environmental and occupational health students in Ardabil University of Medical Sciences, Iran, toward their chosen field of study due to the content and functional similarities between these two majors.…”
Section: Introductionmentioning
confidence: 99%